Disiplin Belajar, Lingkungan Kelas, Perhatian Orang Tua sebagai Upaya Meningkatkan Hasil Belajar IPS - Solikhin Solikhin; Tarto Sentono (UM Purwokerto Press, 2022)
This study aims to determine the positive influence student learning discipline, classroom environment on learning outcomes in subjects in class IV SDN Bratasena. The population in this study were all students of class IV SDN Bratasena 2021/2022 total as many as 188 students. Determination of the sample is done with purposive sampling technique; namely the sample is determined by the investigators. In this study, researchers took samples based classes with setting Tourism IV as samples, amounting to a total of 100 students.